Integrated Pest and Disease Management: A Sustainable Approach to Crop Protection - Nayak, B. B.; Sree Pooja, G.; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2021)
Agricultural productivity is increasingly threatened by pests and diseases, causing 20-40% of global crop yield losses annually. Conventional pest and disease management relies heavily on synthetic pesticides and fungicides, leading to pesticide resistance, environmental degradation, biodiversity loss, and human health risks. As global pesticide consumption continues to rise, concerns over economic costs and sustainability have intensified. As a leading agricultural nation, India faces similar challenges with increasing pesticide dependence, farmer health risks, and environmental pollution. Integrated Pest and Disease Management (IPDM) is emerging as a holistic, eco-friendly alternative that integrates biological control, cultural practices, mechanical interventions, and judicious chemical use to ensure long-term agricultural resilience. This manuscript explores the global and Indian perspectives on pesticide use, the economic and environmental impacts of conventional pest management, and the broad strategies of IPDM. Additionally, it highlights IPDM’s alignment with Sustainable Development Goals (SDGs) and discusses challenges and prospects for its implementation.